PEMBERDAYAAN MASYARAKAT PESISIR DESA BATU ATAS BARAT, KECAMATAN BATU ATAS, KABUPATEN BUTON SELATAN ELALUI OPTIMALISASI POTENSI SUMBER DAYA LAUT YANG BERKELANJUTAN - Deki Pradana; Said Sales Salihi (JICS : Journal Of International Community Service, 2025)
This Community Service Program (PKM-PM) focuses on empowering the coastal community of Batu Atas Barat Village, which often faces economic limitations and a reliance on raw, unprocessed marine catches. The potential of abundant marine resources has not been optimally utilized to improve community welfare. The program's implementation method includes three main activities: (1) Education and Training, comprising counseling on the importance of coastal ec osystem conservation and training in diversifying processed seafood to increase its market value; (2) Application of Appropriate Technolo gy, introducing energy-efficient fish drying and preservation tools to reduce post-harvest losses; and (3) Digital Marketing Assistance, helping the community market processed products through social media platforms and e-commerce. This program is expected to empo wer the community by creating sustainable livelihoods, reducing mari ne product waste, and building economic independence. The long-term goal is to establish a self-reliant and prosperous coastal village through responsible and sustainable marine resource management.